2003
DOI: 10.1029/2002jc001619
|View full text |Cite
|
Sign up to set email alerts
|

Observing ocean heat content using satellite gravity and altimetry

Abstract: [1] A method for combining satellite altimetry observations with satellite measurements of the Earth's time-varying gravity to give improved estimates of the ocean's heat storage is presented. Over the ocean the time-variable component of the geoid can be related to the time-varying bottom pressure. The methodology of estimating the ocean's time-varying heat storage using altimetric observations alone is modified to include observations of bottom pressure. A detailed error analysis of the methodology is undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…Over the ocean, these mass variations represent fluctuations in ocean bottom pressure [e.g., Jayne et al, 2003]. Chambers et al [2004] first demonstrated that GRACE could measure the variation in the global mean ocean mass (OBP) quite accurately.…”
Section: Obp and Tws From Gracementioning
confidence: 99%
“…Over the ocean, these mass variations represent fluctuations in ocean bottom pressure [e.g., Jayne et al, 2003]. Chambers et al [2004] first demonstrated that GRACE could measure the variation in the global mean ocean mass (OBP) quite accurately.…”
Section: Obp and Tws From Gracementioning
confidence: 99%
“…In our analysis, the estimates of the sea level anomaly are 3.7 cm on average (Figure 3), which is closer to the point RMS errors of about 3 cm in [31].…”
Section: A Priori Constraintmentioning
confidence: 51%
“…Expressed in terms of equivalent water thickness, the time-varying OBP is related to sterically corrected altimeter data at a certain point [31,32]:…”
Section: Ocean Bottom Pressure and Satellite Altimetrymentioning
confidence: 99%
“…In the future, these hydrographic cruises must be augmented by an array of deep floats, moored instruments, gliders, or a combination thereof (e.g., [53]). Improvements in remotely sensed measurements of vertically integrated ocean mass (or equivalently bottom pressure, see [22]) such as from the proposed GRACE-II mission could also help constrain the deep density field when combined with sea level and upper ocean information.…”
Section: Figure 4 the Number Of Global Temperature Observations Per mentioning
confidence: 99%
“…Salinity data from CTDs and velocity data from current meters and acoustic Doppler current profilers (ADCPs) are usually used for validation. Gravity measurements from the Gravity Recovery and Climate Experiment (GRACE) and the newly launched Gravity field and steady-state Ocean circulation Explorer (GOCE) provide estimates of the geoid for use with altimetry as well as derived bottom pressure estimates (e.g., [22], [23]). …”
Section: The Current Global Synthesis Effortsmentioning
confidence: 99%